Tested by Zion : The Bush Administration and the Israeli-Palestinian Conflict / [electronic resource] - Abrams, Elliott (Cambridge : Cambridge University Press, 2013)
This book tells the full inside story of the Bush Administration and the Israeli-Palestinian conflict. Written by a top National Security Council officer who worked at the White House with Bush, Cheney, and Rice and attended dozens of meetings with figures like Sharon, Mubarak, the kings of Jordan and Saudi Arabia, and Palestinian leaders, it brings the reader inside the White House and the palaces of Middle Eastern officials. How did 9/11 change American policy toward Arafat and Sharon's tough efforts against the Second Intifada? What influence did the Saudis have on President Bush? Did the American approach change when Arafat died? How did Sharon decide to get out of Gaza, and why did the peace negotiations fail? In the first book by an administration official to focus on Bush and the Middle East, Elliott Abrams brings the story of Bush, the Israelis, and the Palestinians to life.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Al-Aqsa Intifada, 2000-